2019
DOI: 10.1080/15295192.2019.1555430
|View full text |Cite
|
Sign up to set email alerts
|

Brain Processes in Mothers and Nulliparous Women in Response to Cry in Different Situational Contexts: A Default Mode Network Study

Abstract: In everyday life, parents must respond to and interact with children while in different situational contexts. How situational contexts influence parents' responses has not been systematically studied. Here we investigated mothers' versus nonmothers' neural responses to infant vocalizations in different situations with different task demands. Design: Using fMRI in 21 women (10 mothers), we explored the effects of being distracted by self-oriented (self-referential decisions about personality adjectives) versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…However, findings of several recent meta-analyses suggest differences in maternal brain responses to visual vs. auditory infant cues. One of the most noticeable differences is that visual cues more robustly activate reward processing regions such as the hypothalamus, ventral tegmental area, nucleus accumbens, and substantia nigra ( Rigo et al, 2019a , Rocchetti et al, 2014 ). Activation in these maternal motivation regions is particularly strong toward visual cues from one’s own infant compared to a control infant ( Paul et al, 2019 , Rocchetti et al, 2014 ).…”
Section: Neural Adaptation To Motherhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…However, findings of several recent meta-analyses suggest differences in maternal brain responses to visual vs. auditory infant cues. One of the most noticeable differences is that visual cues more robustly activate reward processing regions such as the hypothalamus, ventral tegmental area, nucleus accumbens, and substantia nigra ( Rigo et al, 2019a , Rocchetti et al, 2014 ). Activation in these maternal motivation regions is particularly strong toward visual cues from one’s own infant compared to a control infant ( Paul et al, 2019 , Rocchetti et al, 2014 ).…”
Section: Neural Adaptation To Motherhoodmentioning
confidence: 99%
“…Another reason why infant cry sounds do not elicit consistently strong responses in the brain’s reward areas can be that cry sounds are distressing, whereas visual cues can include both positive and distressing stimuli, such as smiling and crying faces. While visual child cues more robustly activate the reward and motivation regions in the brain, infant cry sounds more robustly activate brain regions involved in processing emotional auditory stimuli such as superior temporal gyrus and somatosensory and motor areas such as supplementary motor area and precentral gyrus ( Rigo et al, 2019a , Witteman et al, 2019 ). In a study that included mothers from three different countries (US, Italy, China), increased responses to infant cry sounds in regions across several brain networks including the supplementary motor area and superior temporal gyrus were found among mothers across cultures ( Bornstein et al, 2017 ).…”
Section: Neural Adaptation To Motherhoodmentioning
confidence: 99%
“…Several studies have ascertained that emotional recognition of vocalisations demands attentional [40] and prediction resources [37]. Furthermore, human vocalisations which are salient and convey the emotional state of another person are automatically prioritised when pitted against other competing stimuli for selective attention [15,16,36,39,41]. Therefore, integrating salient vocalisations with the ambiguous and unfamiliar OE contextual scenes could have demanded greater recruitment of the rostrolateral PFC so as to make meaning of both the auditory and visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, context lends interpretation to salient emotional vocalisations. The functional-contextual theory of emotions posits that vocalisations only serve to attract attention and are subsequently interpreted in a context-dependent manner [12][13][14][15][16]. Recently, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Fleming et al, 2002;Van Anders et al, 2012) and neural processing (e.g. Rigo et al, 2019), are found in a wide variety of mammals regardless of parenting status. However, these processes show some disparities for males and females, as well as for parents and non-parents (e.g.…”
Section: Introductionmentioning
confidence: 99%